Audit Expectation Gap, Auditors' Statutory Duty and Financial Reporting Quality in Nigeria - Sani Alfred Ilemona; Ikpor I.M. (Universitas Padjadjaran, 2023)
The study examined the impact of the audit expectation gap and auditors' statutory duty on financial reporting quality in Nigeria. Data for the study were obtained primarily through questionnaires administered to randomly selected 400 respondents comprising auditors, accountants, stockbrokers, and investors in various sectors of the Nigerian economy. Of the distributed questionnaires, 252 were received, representing a 63 per cent response rate. Multiple regression and t-statistical tools were employed to analyze the responses to the questionnaire designed to reflect five (5) Likert Scale on the impact of audit expectation gap and statutory duty of auditors (explanatory variables) on financial reporting quality (dependent variable). The results indicated that all the independent variables significantly impact the dependent variable. The study recommended, among others, that auditors' responsibility/duty should be expanded through legislation to capture/include the implicit expectation of the ways audit expectations in Nigerian society.